2017
DOI: 10.18632/oncotarget.19854
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of GDF11 expression and synaptic plasticity by age and training

Abstract: The Growth Differentiation Factor 11 (GDF11) has been controversially involved in the aging/rejuvenation process. To clarify whether GDF11 is differently expressed during aging, we have evaluated GDF11 levels in skeletal muscles and hippocampi of young and old mice, sedentary or subjected to a 12-weeks triweekly training protocol. The results of real-time PCR and Western blot analyses indicate that skeletal muscles of sedentary old mice express higher levels of GDF11 compared to young animals (p < 0.05). Conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 40 publications
4
17
0
Order By: Relevance
“…Whether endogenous GDF11 influences neuronal activity, including neurogenesis and synaptic transmission, under normal conditions in the adult brain is less clear. One study that relied on antibody-based detection found that GDF11 expression does not correlate with synaptic plasticity, as measured by long-term potentiation physiology assessment (De Domenico et al 2017). Surprisingly, hippocampal GDF11 levels decreased in aged mice following rotarod training, although the causes and implications of such a reduction in response to physical exercise are unknown (De Domenico et al 2017).…”
Section: Gdf11 In Brain Aging and Disease Modelsmentioning
confidence: 99%
“…Whether endogenous GDF11 influences neuronal activity, including neurogenesis and synaptic transmission, under normal conditions in the adult brain is less clear. One study that relied on antibody-based detection found that GDF11 expression does not correlate with synaptic plasticity, as measured by long-term potentiation physiology assessment (De Domenico et al 2017). Surprisingly, hippocampal GDF11 levels decreased in aged mice following rotarod training, although the causes and implications of such a reduction in response to physical exercise are unknown (De Domenico et al 2017).…”
Section: Gdf11 In Brain Aging and Disease Modelsmentioning
confidence: 99%
“…A wide variation of GDF11 protein expression was detected in the hippocampus of old animals. Moreover, interestingly, GDF11 appeared to be differently modulated by exercise in the hippocampus of young and old mice [21]. A recent study established that GDF11 enhanced hippocampal neurogenesis and plasticity in the hippocampus and cortex of old mice [22].…”
mentioning
confidence: 99%
“…We observed that none of the differences in Gdf11 expression between skeletal muscles from young and aged mice were statistically significant at the mRNA level (Figure 3A). Because the detection of GDF11 protein has been controversial (Egerman et al, 2015; Smith et al, 2015), we performed western blotting with two different antibodies purchased from R&D Systems and Abcam (Figure 3B) that were used in previous studies (Sinha et al, 2014; De Domenico et al, 2017). The differences in the GDF11 protein levels in the mice skeletal muscles of the young and aged, detected with both the R&D (Figure 3C) and Abcam (Figure 3D) antibodies, were not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…However, we observed no changes in GDF11 expression in the skeletal muscle with aging. The expression of GDF11 in skeletal muscle was previously investigated in the gastrocnemius and quadriceps muscles (Egerman et al, 2015; Poggioli et al, 2016; De Domenico et al, 2017), which are composed of both slow- and fast-twitch muscle fibers. Previous studies have reported that Gdf11 mRNA in those muscles increased (Egerman et al, 2015; De Domenico et al, 2017) or did not change (Poggioli et al, 2016) with aging.…”
Section: Discussionmentioning
confidence: 99%